Cognitive screening considerations for psychosocial clinical trials in HIV, aging, and cognition. (April 2023) - Eaton, Andrew D; Chan Carusone, Soo; Murzin, Kate; Hui, Jenny; McCullagh, John W; Walmsley, Sharon L
Cognitive impairment is a common comorbidity among individuals aging with HIV, which can be an extreme source of stress and anxiety for many. Psychosocial interventions have the potential to alleviate symptoms associated with cognitive impairment and help improve the quality of life of people with HIV as they continue to age; these interventions are in the infancy of development and require further testing via clinical trials. The slow development of interventions may be partially attributed to a common trend of requiring a formal HIV-associated neurocognitive disorder diagnosis to qualify for psychosocial clinical trials. HIV-associated neurocognitive disorder is diagnosed through intensive, time-consuming tests, and still many cases of HIV-associated neurocognitive disorder remain undiagnosed, misdiagnosed, or misclassified due to the limitations of the assessment process. This commentary suggests an alternate method of screening for cognitive impairments through the use of a brief, low-barrier assessment, alongside validity considerations. Such alternate screening may improve enrollment and completion rates in psychosocial clinical trials for people aging with HIV and cognitive impairment, by removing the burden of extensive testing that is commonly associated with an HIV-associated neurocognitive disorder diagnosis from clinical trial eligibility, while still providing valuable insight into individuals' cognitive functioning.